Nondestructive estimation of shoot nitrogen in different rice genotypes - Ladha, Jagdish K.; Tirol-Padre, Agnes; Punzalan, Gloria C.; Castillo, E.; Singh, Upendra; Reddy, C. Kesava (Wiley, 1998)
Plant N uptake and grain yield are important components of N use efficiency. Grain yield is easily measured, but plant N analysis is time consuming and requires hazardous chemicals or expensive equipment. A nondestructive method involving the least equipment and skill, to determine N uptake, is needed in agronomic and plant breeding experiments. A nondestructive method to determine shoot (aboveground biomass) N of transplanted rice (Oryza sativa L.) was developed based on SPAD‐502 chlorophyll meter readings, leaf area, and tiller number. In two dry‐season and one wet‐season field experiment, shoot N of various genotypes at flowering were highly correlated (P < 0.05) with CLAT, the product of SPAD reading from a selected leaf (C), area of that leaf (LA), and number of tillers (T) (r2 = 0.46, 0.90, and 0.85 in Exp. 1, 2, and 3, respectively); and with LAT, the product of LA and T (r2 = 0.56, 0.88, and 0.76). Shoot N may be estimated using LAT for larger differences in leaf area compared with SPAD readings. Lower correlations in Exp. 1 were due to the lower range in shoot N contents. The highest correlation between shoot N and CLAT was observed in the third uppermost leaf. Regressions of shoot N on LAT and CLAT varied across growth stages and seasons. Thus, LAT or CLAT can be used to evaluate N uptake among N fertilizer treatments and different rice genotypes at a given stage within a season. Further work is needed to assess the reliability of this method under different seasons and cultural practices.